Perceived Health Impacts of Teenage Pregnancy among Married Adolescents in Peri-urban Areas of Kathmandu Valley - Neupane, Ishwer Prasad (Journal of Health Promotion, 2018)
Teenage pregnancy is an issue that calls for more education and support to encourage girls to delay motherhood until they are ready. The developing countries have a large proportion of young people in the world and teenage pregnancy has emerged as one of the major public health problems. The objective of this research paper is to identify the health problems, and social consequences associated with teenage pregnancy with particular reference of peri-urban dwellers in the Kathmandu Valley. A rural health centre based cross sectional study was done with 15-19 years old 300 teenage pregnant girls as subject of the research. Peri-urban areas were purposively selected from Lalitpur District and the samples were selected from the health care centre records. The sampled units were interviewed by using standardized semi-structured questionnaire at their place of residents.Journal of Health Promotion Vol.6 2008, p.23-27